The effectiveness of a scaffolded problem-based learning model to enhance systematic thinking and learning achievement in a Thai higher education database systems course - Budsara, Kridsada; Petsangsri, Sirirat; Ratanaolarn, Thanin (Edelweiss Applied Science and Technology, 2025)
The global digital skills gap, particularly in roles such as data engineering and system analysis, highlights the necessity for effective pedagogy in foundational courses like database systems. Students often encounter difficulties with the higher-order thinking skills (HOTS) required for database design and SQL programming. Consequently, this study developed and evaluated the effectiveness of a Scaffolded Problem-Based Learning (PBL) model, termed the ‘KRIS model,’ aimed at improving students' systematic thinking and academic achievement. The KRIS model was constructed through a synthesis of PBL, scaffolding literature, and prior research on student perceptions. It comprises four core components: (K) Knowledge base support, (R) Responsibility for self and collaboration, (I) Inter-connectedness in team interaction, and (S) Systematic process. The model was validated by a panel of seven experts specializing in database systems, PBL, and assessment. A quasi-experimental design was employed, comparing an experimental group (n=60) taught with the KRIS model against a control group (n=59) taught using traditional methods. Expert validation confirmed the model's high quality and suitability. The experimental results indicated that students in the experimental group, who learned through the KRIS Scaffolded PBL model, achieved significantly higher scores in both systematic thinking and academic achievement than those in the control group. The KRIS Scaffolded PBL model is an effective instructional strategy for enhancing higher-order cognitive outcomes in database education. It offers a structured framework to support learners, fostering systematic thinking and practical skills essential for the modern ICT (information communications technology) industry.